2018
DOI: 10.1016/j.pscychresns.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Network abnormalities in generalized anxiety pervade beyond the amygdala-pre-frontal cortex circuit: Insights from graph theory

Abstract: Generalized anxiety disorder (GAD) has excessive anxiety and uncontrollable worry as core symptoms. Abnormal cerebral functioning underpins the expression and perhaps pathogenesis of GAD:. Studies implicate impaired communication between the amygdala and the pre-frontal cortex (PFC). Our aim was to longitudinally investigate whether such network abnormalities are spatially restricted to this circuit or if the integrity of functional brain networks is globally disrupted in GAD. We acquired resting-state functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…We may hypothesize that individuals with intellectual disabilities are more likely to have genetic conditions linked to higher risk for other medical conditions. Individuals with intellectual disabilities or anxiety disorders may also be less likely to adequately communicate their symptoms and distress to care providers ( 58 , 59 , 60 , 61 ). Patient complaints may also be wrongly attributed to these conditions or considered as exaggerated in these patients, despite their elevated risk of death as suggested by our findings, which may lead to less thorough medical evaluation and worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…We may hypothesize that individuals with intellectual disabilities are more likely to have genetic conditions linked to higher risk for other medical conditions. Individuals with intellectual disabilities or anxiety disorders may also be less likely to adequately communicate their symptoms and distress to care providers ( 58 , 59 , 60 , 61 ). Patient complaints may also be wrongly attributed to these conditions or considered as exaggerated in these patients, despite their elevated risk of death as suggested by our findings, which may lead to less thorough medical evaluation and worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The amygdala is located on the medial dorsal side of the anterior temporal lobe and is a part of the limbic system. Functional brain imaging studies showed that the level of amygdala activation was higher in anxious patients than in healthy controls; moreover, increased amygdala response in clinical and healthy individuals was associated with trait anxiety (36). Makovac et al found reduced connections of the amygdala to the prefrontal cortex in people with generalized anxiety disorders (36).…”
Section: Amygdalamentioning
confidence: 99%
“…Functional brain imaging studies showed that the level of amygdala activation was higher in anxious patients than in healthy controls; moreover, increased amygdala response in clinical and healthy individuals was associated with trait anxiety (36). Makovac et al found reduced connections of the amygdala to the prefrontal cortex in people with generalized anxiety disorders (36). Similarly, Xue et al found that high state anxiety level was associated with decreased connectivity of the amygdala to the precuneus/posterior cingulate cortex in adults with anxiety disorders (37).…”
Section: Amygdalamentioning
confidence: 99%
“…significantly increased network segregation was observed in GAD [45], and sub-optimal brain-wide organization and integration was present in patients with GAD [46]. Interestingly, a number of studies have also failed to find any global network differences in anxiety disorders: the network structure and node centrality metrics did not differ between the SAD and healthy groups [47]; the global network strength of anxiety symptoms did not change significantly in eating disorder psychopathology before and after treatment [48].…”
Section: Plos Onementioning
confidence: 97%